Short-run distributional effects of public education in Greece - Christos Koutsampelas; Panos Tsakloglou (Institute for the Study of Labor (IZA), 2012)
The present paper examines the short-run distributional impact of public education in Greece using the micro-data of the 2004/5 Household Budget Survey. The aggregate distributional impact of public education is found to be progressive although the incidence varies according to the level of education under examination. In-kind transfers of public education services in the fields of primary and secondary education lead to a considerable decline in relative inequality, whereas transfers in the field of tertiary education appear to have a small distributional impact whose size and sign depend on the treatment of tertiary education students living away from the parental home. When absolute inequality indices are used instead of the relative ones, primary education transfers retain their progressivity, while secondary education transfers appear almost neutral and tertiary education transfers become quite regressive. Finally, we use the EUROMOD tax-benefit microsimulation model in order to estimate the first-round distributional effects of a graduate tax imposed on the current stock of graduates. The main policy implications of the findings are outlined in the concluding section.
urn:nbn:de:101:1-201203145324
Keywords: I24; D31; 330; public education; redistribution; Greece; Allgemeinbildende Schule; Öffentliche Bildungsausgaben; Verteilungswirkung; Griechenland